A influência da pergunta do aluno na aprendizagem :o questionamento na sala de aula de química e o educar pela pesquisa - Camargo, Andrea Norema Bianchi de (2015)
The study on the influence of the student's question on learning in Chemistry in action research in the classroom contribute to answer the following question: how the elaboration and discussion of questions for high school students contribute to their learning in chemistry? The research was conducted with students of the 3rd year of high school at a private school of the Porto Alegre city. Initially, the research subjects proposed questions about what they would like to know about alcohol. The questions were analyzed, categorized and served the basis for the organization of a Learning Unit (AU). Based on frequently asked questions, was developed and applied an initial test to identify the knowledge of the students. After completion of the activities of the AU, in order to build students' answers to questions, a final test was applied, similar to the initial test. Thus, we performed a comparative analysis between the two tests. A questionnaire was also on the perceptions of students in relation to the fact studying chemistry from their own questions. The investigation allowed us to consider the questions of the students contribute to their learning because mobilize their curiosity, influencing him to take up subjects of their learning. Allowed the reconstruction of knowledge under the theme generator in a broad perspective (scientific, technological and social), as it was associated with students' experiences and their daily lives. The dialogue with the teacher and classmates, aiming to construct answers to questions stimulated the construction of arguments, so that the teaching of chemistry began to have meaning for students.